(untitled) (Modern education and development, 2025)
This study investigates the impact of podcasts on improving pronunciation accuracy among 10th-grade EFL students. Pronunciation, a vital component of effective communication, is often neglected in traditional language learning settings, leading to challenges for high school learners. The research focuses on evaluating the current pronunciation competence of students and the effectiveness of podcasts as a pedagogical tool. A total of 30 students from Grade 10 at School 79 in Tashkent participated in the study, divided equally into control and experimental groups. Over a four-week period, the experimental group engaged in podcast-based learning, while the control group followed conventional methods. Data collection involved pre-tests, post-tests, and questionnaires to assess changes in pronunciation competence and students’ perceptions of podcast usage. Statistical analyses were conducted to compare the outcomes of the two groups. The findings aim to provide insights into how digital tools like podcasts can enhance language learning, offering practical implications for educators seeking innovative methods to improve students’ pronunciation skills.